Semantic and Syntactic Features of Constructions with the Meaning of Measure and Degree in Russian - I. V. Semenova (Научный диалог, 2021)
The syntactic structures, that are intended in Russian to express the meaning of measure and degree, are discussed in the article. The relevance of the study is due to the problems of modern syntax, which is aimed at a multidimensional analysis of syntactic structures and the study of the functions of service words involved in their organization. The work was carried out in the traditions of the Vladivostok scientific school, which applied the “from construction” approach to the analysis of syntactic units. It is indicated that this term is used here in a narrow sense as a structure embedded in a complex sentence, having a certain set of components and a specific means of connecting these components. The novelty of the research is determined by the use of the concept of “construction” as the main tool for analyzing syntactic units with the meaning of measure and degree in the formal grammatical aspect. A features analysis of the formation of the semantics of measure and degree within the framework of syntactic structures is presented, the formal organization of these structures is described in detail: the component composition, the “core” of the structure — service complexes used to link components, the role of clarifiers and the possibility of phraseologization of the structure. It is noted that this study is important both for solving theoretical issues that relate to a versatile description of syntactic structures, and for teaching the syntax of the Russian language to foreign students.